Impact of Guidelines on the Diffusion of Medical Technology: A Case Study of Cardiac Resynchronization Therapy in the UK - Rucha Vadia; Tom Stargardt (Applied Health Economics and Health Policy, 2020)
Introduction Research on clinical practice guidelines as a determinant of the diffusion of medical technology remains sparse. We aim to evaluate the impact of guidelines on the awareness of medical technology, as a proxy of its use, with the example of cardiac resynchronization therapy (CRT) in the United Kingdom (UK). Methods We measured clinician awareness based on Google searches performed for CRT that corresponded with actual CRT implant numbers provided by the European Heart Rhythm Association (EHRA). We identified the guideline recommendations published by the National Institute of Health and Care Excellence (NICE) within the UK, the European Society of Cardiology~(ESC) at the European level, and the American College of Cardiology Foundation/American Heart Association in the United States (US). We specified a dynamic moving average model, with Google searches as the dependent variable and guideline changes as the independent variables. Results One guideline change published by NICE in 2007 and two changes released by the US guidelines in 2005 and 2012 were significantly correlated with the Google searches (p0.167em=0.167em0.08, p0.167em=0.167em0.02, and p0.167em=0.167em0.02, respectively). Guideline changes by the ESC had no significant impact. Changes recommending CRT in place of a conventional pacemaker, in patients with atrial fibrillation, and restricting CRT due to contraindication, remained universally uninfluential. Conclusion The factors associated with a lack of awareness (as a proxy for technology diffusion) in our case study were: a lack of strong clinical evidence that resulted in the moderate strength of a recommendation, a lack of recognition of any externally published recommendation by NICE, and the frequent release of guidelines with minor changes targeting small patient groups. At least in our case, in the absence of NICE guidelines, the US guidelines received more attention than their non-UK European counterparts, even if the former were released after the latter.
Keywords: 610; Pharmacoeconomics and Health Outcomes; Quality of Life Research; Health Economics; Health Administration; Public Health